Spontaneous healing of Mycobacterium ulcerans disease in Australian patients. - Daniel P O'Brien; Adrian Murrie; Peter Meggyesy; Jonathan Priestley; Avinash Rajcoomar; Eugene Athan (Public Library of Science (PLoS), 2019)
BACKGROUND:Mycobacterium ulcerans causes necrotising infections of skin and soft tissue mediated by the polyketide exotoxin mycolactone that causes cell apoptosis and immune suppression. It has been postulated that infection can be eradicated before the development of clinical lesions but spontaneous resolution of clinical lesions has been rarely described. METHODOLOGY/PRINCIPAL FINDINGS:We report a case series of five Australian patients who achieved healing of small M. ulcerans lesions without antibiotics or surgery. The median age of patients was 47 years (IQR 30-68 years) and all patients had small ulcerative lesions (median size 144mm2, IQR 121-324mm2). The median duration of symptoms prior to diagnosis was 90 days (IQR 90-100 days) and the median time to heal from diagnosis without treatment was 68 days (IQR 63-105 days). No patients recurred after a median follow-up of 16.6 months (IQR 16.6-17.9 months) from the development of symptoms and no patients suffered long-term disability from the disease. CONCLUSIONS:We have shown that healing without specific treatment can occur for small ulcerated M. ulcerans lesions suggesting that in selected cases a robust immune response alone can cure lesions. Further research is required to determine what lesion and host factors are associated with spontaneous healing, and whether observation alone is an effective and safe form of management for selected small M. ulcerans lesions.